Edukasi Membangun Kesadaran Anti-Bullying di Sekolah pada Siswa SMP Muhammadiyah 2 Kalasan - Daviddefikry Yondra Perdana; Anisa Yusitarini; Naqisshi Ummu Istighfari; Triantoro Safaria (Jurnal Kabar Masyarakat, 2023)
Bullying connotes actions taken intentionally to give other people a feeling of discomfort by berating, demeaning, criticizing, nicknamed, kicking, pushing, depriving money, avoiding, and refusing to make friends is a real form of action. The purpose of this Community Empowerment Program (Podamat) is to provide knowledge about the factors that cause bullying that occurs at Muhammadiyah 2 Kalasan Middle School, provide knowledge about the impacts caused by bullying that occurs at Muhammadiyah 2 Kalasan Middle School, and provide education to students to build Anti-Bullying awareness at SMP Muhammadiyah 2 Kalasan. The results of the Prodamat activity (Community Empowerment Program) entitled "Education to Build Anti-Bullying Generations have had a positive impact, namely increasing insight and better understanding of students at SMP Muhammadiyah 2 Kalasan regarding bullying compared to before receiving this education. This increased understanding includes definitions, types, causal factors, characteristics of perpetrators, victims, witnesses, then knowing the harmful effects of bullying behavior.